VALIDATION OF THE URDU VERSION OF EPIDEMIC PANDEMIC IMPACT INVENTORY AMONG PAKISTANI ADULTS - Rabia Khawar; Hussain, Samavia; Imran, Nazish; Haider , Imran Ijaz (Journal of Pakistan Psychiatric Society, 2022)
Background: The current research aimed at evaluating the psychometric properties of the EPII-Urdu version by analyzing reliability and construct validity among Pakistani population. Method: A convenient sample of 580 individuals above age 18 (M = 27.38, SD = 9.19) was drawn from different areas of two cities, Lahore and Faisalabad (Pakistan). First of all, written informed consent was given to the participants to follow ethical standards. Translated Urdu versions of The Epidemic Pandemic Impact Inventory, Flourishing Scale, WHO Brief Quality of Life Questionnaire, Depression Anxiety Stress Scale (DASS-21), and demographic sheet were applied to the participants. Results: Results indicated excellent internal consistency of overall EPII Urdu version (α = .92); while all the subscales of EPII showed good alpha reliability coefficients [work (α = .75), Education & Training (α = .73), Home Life (α = .78), Social Activities (α = .78), Economic (α = .70), Emotional Health & Wellbeing (α = .73), Physical Health Problems (α = .71), Physical Distance & Quarantine (α = .81), Infection History (α = .74) and Positive Change (α = .76)]. Findings of test-retest reliability with a gap of three weeks on 31 participants were found to be satisfactory. Positive correlation of EPII Urdu version with subscales of DASS-21 and negative relationship with Flourishing Scale, and WHO BRIEF-QoL provided evidences for convergent and divergent validities respectively for Urdu version of EPII. Conclusion: Findings indicated that the EPII Urdu version proved to be a psychometrically sound instrument for measuring the impacts of COVID-19 among Pakistani population.